ENRICH: The Developed English Grade 8 Most Essential Learning Competencies-Based and Integration-Focused Worksheets - Margielyn M Angay (Research Synergy Foundation, 2023)
This paper presents the development and validation of an English Grade 8 Worksheet aligned with the Most Essential Learning Competencies (MELCs) and emphasizing integration across subjects. A quantitative research design was employed to assess these worksheets' content validity and acceptability. The evaluation used simple mean and four-point Likert scales to gauge validity and acceptability. Additionally, a T-test was conducted to determine if there was a significant difference in learner performance between their pretest and posttest. The assessment involved various education professionals, including head teachers, master teachers, subject-specific teachers, and program supervisors. Remarkably, all evaluators unanimously rated the content validity of the worksheets as